2008
DOI: 10.1111/j.1469-7998.2008.00427.x
|View full text |Cite|
|
Sign up to set email alerts
|

Anhydrobiosis in tardigrades and its effects on longevity traits

Abstract: Living in harsh and variable environments that are prone to periodic desiccation, tardigrades exhibit remarkable tolerance against physical extremes through a state known as anhydrobiosis. To study the effect of this state on the longevity and hence the lifecycle in the taxon Tardigrada for the first time, we exposed a tardigrade species, Milnesium tardigradum, to alternating periods of drying and active feeding periods in a hydrated state. Compared with a hydrated control, the periodically dried animals showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 26 publications
(43 reference statements)
2
74
1
1
Order By: Relevance
“…This is detectable when age-specific traits are analysed Ricci & Pagani 1997;Ricci 2001;Ricci & Covino 2004;Ricci & Caprioli 2005;Ricci & Perletti 2006). A recent study on another group of anhydrobiotic micrometazoans, the tardigrades, has shown that this taxon, as well, behaves like a sleeping beauty (Hengherr et al 2008). …”
Section: Dormancy: the Most Distinctive Unusual Feature Of Bdelloidsmentioning
confidence: 99%
“…This is detectable when age-specific traits are analysed Ricci & Pagani 1997;Ricci 2001;Ricci & Covino 2004;Ricci & Caprioli 2005;Ricci & Perletti 2006). A recent study on another group of anhydrobiotic micrometazoans, the tardigrades, has shown that this taxon, as well, behaves like a sleeping beauty (Hengherr et al 2008). …”
Section: Dormancy: the Most Distinctive Unusual Feature Of Bdelloidsmentioning
confidence: 99%
“…The survival of desiccated tardigrades under atmospheric oxygen conditions can be long (nine years) but seems not to exceed 20 years (Baumann, 1927;Guidetti and Jönsson, 2002;Rebecchi et al, 2006;Jørgensen et al, 2007). This means that during anhydrobiosis some damages occur leading to the death of tardigrades (Rebecchi et al, 2006), even though desiccation does not seem to have an effect on their aging and longevity because under alternating periods of desiccation (seven days) and of active life (seven days) the time spent in anhydrobiosis is ignored (Hengherr et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…In the anhydrobiotic state, their metabolism is barely measurable (Pigoń and Węglarska 1955). The longer the animals spend in this state of suspended animation, the longer their lifespan (Hengherr et al 2008a). The animals resume activity after successful rehydration.…”
Section: Introductionmentioning
confidence: 99%